Chronic febrile patient – evaluation of cause and management - Kucharz, Eugeniusz (Przewodnik Lekarza/Guide for GPs, 2010)
Fever is deregulation of core temperature of body due to alterations in the thermoregulatory center and is a complex pathophysiological response leading to increase in set point of temperature regulation. Clinical course of fever may be different (fever continuous, fever remittent, fever intermittent, fever hectic). Causes of fever include infections, neoplasms, immunological, metabolic and endocrine disturbances and others. Hereditary recurrent fever is found in patients with autoimmune or autoinflammatory syndromes (familial Meriderranean fever, cryopyrinopathies: familial cold utricaria, Mucke-Wells syndrome and chronic infantile neurological cutaneous and articular syndrome or neonatal-onset mulitsystemic inflammatory disease, the TNF-receptor-associated autoinflammatory syndrome, NALP12-associated periodic fever and others).